Energetic particle signatures of magnetic field‐aligned potentials over Jupiter's polar regions - Clark, G.; Mauk, B. H.; Haggerty, D.; Paranicas, C.; Kollmann, P.; Rymer, A.; Bunce, E. J.; Cowley, S. W. H.; Mitchell, D. G.; Provan, G.; Ebert, R. W.; Allegrini, F.; et al. (Geophysical research letters, 2017)
Recent results of the first ever orbit through Jupiter's auroral region by NASA's Juno spacecraft did not show evidence of coherent acceleration in the auroral or polar region. However, in this letter, we show energetic particle data from Juno's Jupiter Energetic‐particle Detector Instrument instrument during the third auroral pass that exhibits conclusive evidence of downward parallel electric fields in portions of Jupiter's polar region. The energetic particle distributions show inverted‐V ion and electron structures in a downward electric current region with accelerated peaked distributions in hundreds of keV to ~1 MeV range. The origin of these large electric potential structures is investigated and discussed within the current theoretical framework of current‐voltage relationships at both Earth and Jupiter. Parallel electric fields responsible for accelerating particles to maintain the aurora/magnetospheric circuit appear to be a common phenomenon among strongly magnetized planets with conducting ionospheres; however, their origin and generation mechanisms are subjects of ongoing research. Key Points Evidence of magnetic field‐aligned electric potentials above portions of Jupiter's polar cap regions Electrons show upward peaked energy distributions of several hundreds of keV Ions (H+, On+, and Sn+) show downward peaked energy distributions from hundreds of keV to a few MeV